Exposure to oral contraceptives increases the risk for development of inflammatory bowel disease: a meta-analysis of case-controlled and cohort studies. Issue 9 (September 2017) - Ortizo, Ronald; Lee, Stephanie Y.; Nguyen, Emily T.; Jamal, Mohammad Mazen; Bechtold, Matthew M.; Nguyen, Douglas L.
Abstract : Background: The oral contraceptive pill (OCP) is a widely used method of contraception. There have been conflicting studies linking the use of OCPs to the development of inflammatory bowel disease (IBD). The intent of this meta-analysis is to better define the association between OCP exposure and the risk for development of IBD. Methods: A thorough search of multiple databases, including Scopus, Cochrane, MEDLINE/PubMed, and CINAHL, and abstracts from major gastroenterology meetings was performed (October, 2016). Studies reporting the development of IBD in patients with or without previous exposure to OCP, compared with healthy controls, were included. A meta-analysis was completed using the Mantel–Haenszel model to evaluate the risk of developing IBD in the setting of previous OCP exposure. Results: In a complete analysis of 20 studies, there appeared to be over a 30% increased risk for the development of IBD in patients exposed to OCP compared with patients not exposed to OCP [odds ratio (OR): 1.32, 95% confidence interval (CI): 1.17–1.49, P <0.001, I 2 =14%]. More specifically, there was a 24% higher risk for developing Crohn's disease (OR: 1.24, 95% CI: 1.09–1.40, P <0.001; I 2 =38%) and a 30% higher risk for developing ulcerative colitis (OR: 1.30, 95% CI: 1.13–1.49, I 2 =26%) in patients exposed to OCP compared with those not exposed to the medication. Conclusion: The use of OCP is associated with an increased risk for development of Crohn's disease and ulcerative colitis in the genetically susceptible host. The total duration, dose of OCP exposure, and the risk for development of IBD need to be better characterized.